Matrix Metalloproteinase System Deficiencies and Matrix Degradation - Lijnen, H.R.; Collen, D. (Thrombosis and Haemostasis, 1999)
Matrix metalloproteinases (MMPs) constitute a tightly regulated family of enzymes that degrade most components of the extracellular matrix. They are classified based on substrate specificity. Collagenases (MMP-1, interstitial collagenase, EC 3.4.24.7; MMP-8, neutrophil collagenase, EC 3.4.24.34; MMP-13, collagenase-3) degrade connective tissue collagens. Gelatinases (MMP-2, gelatinase A, EC 3.4.24.24; MMP-9, gelatinase B, EC 3.4.24.35) degrade collagen types IV, V, VII and X, elastin, and denatured collagens. Stromelysins (MMP-3, stromelysin-1, EC 3.4.24.17; MMP-10, stromelysin-2, EC 3.4.24.22) and matrilysin (MMP-7, EC 3.4.24.23) degrade the proteoglycan core proteins, laminin, fibronectin, elastin, gelatin, and nonhelical collagen, whereas stromelysin-3 (MMP-11) does not degrade any of the major extracellular matrix components. Macrophage metalloelastase (MMP-12, EC 3.4.24.65) degrades insoluble elastin, collagen IV, fibronectin, laminin, entactin, and proteoglycans.1-7 About 20 members of the MMP family have been identified, including at least four membrane-type (MT) MMPs.8-13MMPs are generally secreted as zymogens that are extracellularly activated by organomercurial compounds, several proteinases (including plasmin, trypsin, chymotrypsin, kallikrein, cathepsin G, or neutrophil elastase), oxygen free radicals, or by association with the cell surface.1,5,6 Active MMPs are inhibited by specific tissue inhibitors of MMPs (TIMPs) via formation of a noncovalent stoichiometric complex.5,6 Four members of the TIMP family have been identified, of which TIMP-1, synthesized by most types of connective tissue cells and by macrophages, acts against all members of the collagenase, stromelysin, and gelatinase classes.2,14,15MMPs are mainly involved in the degradation of extracellular matrix components, but may also play a role in activation and processing of cytokines or growth factors,16 in shedding of membrane-bound receptors,17 in liberation of Fas ligand,18 or in activation of tumor necrosis factor-α.19 Degradation of extracellular matrix is required to allow cell migration and tissue remodeling, which play essential roles in many (patho)physiological processes. The role of the plasminogen/plasmin (fibrinolytic) and MMP systems in neointima formation after vascular injury, atherosclerosis, graft arterial disease, myocardial ischemia, angiogenesis, tumor growth and dissemination, infection, and chronic inflammatory disorders of the kidney, lung, gastrointestinal tract, skin, joints, or cornea has recently been reviewed.20 We will discuss some recent data on interactions between the MMP and plasminogen/plasmin systems and their role in neointima formation and atherosclerotic aneurysm formation.